2021
DOI: 10.1038/s41418-021-00887-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting adipocytic discoidin domain receptor 2 impedes fat gain while increasing bone mass

Abstract: Obesity is closely associated with low-bone-mass disorder. Discoidin domain receptor 2 (DDR2) plays essential roles in skeletal metabolism, and is probably involved in fat metabolism. To test the potential role of DDR2 in fat and fat-bone crosstalk, Ddr2 conditional knockout mice (Ddr2Adipo) were generated in which Ddr2 gene is exclusively deleted in adipocytes by Adipoq Cre. We found that Ddr2Adipo mice are protected from fat gain on high-fat diet, with significantly decreased adipocyte size. Ddr2Adipo mice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A limitation of our study is that we used mice with host global DDR2 knockout for our in vivo tumor burden studies. Prior work has shown that DDR2 plays a role in bone development, lipolysis, and ECM deposition in bone and heart [ 51 55 ], so it is possible that DDR2’s role in other cell types contributes to the observed tumor burden phenotype. To clarify the specific role of fibroblast DDR2 in tumor progression, we performed the omental colonization assay and determined that CAF DDR2 and arginase affects the early steps of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is that we used mice with host global DDR2 knockout for our in vivo tumor burden studies. Prior work has shown that DDR2 plays a role in bone development, lipolysis, and ECM deposition in bone and heart [ 51 55 ], so it is possible that DDR2’s role in other cell types contributes to the observed tumor burden phenotype. To clarify the specific role of fibroblast DDR2 in tumor progression, we performed the omental colonization assay and determined that CAF DDR2 and arginase affects the early steps of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested possible direct effects of DDR2 on these cells such as suppression of insulin stimulated tyrosine phosphorylation of the insulin receptor in the 3T3-L1 adipocyte cell line (112). More recently, direct effects of DDR2 on adipocytes in vivo were examined using Adipo Cre ; Ddr2 fl/fl mice, where Ddr2 is inactivated in peripheral as well as marrow fat (113). In this study, mutant mice were protected from high fat diet-induced weight gain, a response that was attributed to decreased adipocyte size.…”
Section: Metabolic Effects Of Ddr2 Deficiency and Relationship To Bon...mentioning
confidence: 92%
“…Mice lacking DDR2 have reduced body mass index and adipose amount compared to wild type mice ( Kawai et al, 2014 ). Moreover, selective deletion of DDR2 in adipose tissue enhances lipolysis via activation of the Adcy5-cAMP-PKA pathway ( Yang et al, 2022 ). Thus, both DDR1 and DDR2 are positive regulators of fatty metabolism and they could contribute to disease by favoring fatty accumulation and increasing extracellular matrix deposition, thus creating a vicious cycle promoting fibrosis.…”
Section: Discoidin Domain Receptors and Metabolismmentioning
confidence: 99%